Strategi BIPP Dalam Meningkatkan Pendapatan Melalui kelompok Tani di Kabupaten Kulon Progo - Is Zunaini Nursinah (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2004)
Research target is to know strategy of BIPP in improving profits farmer group in distric Kulon Progo, by using method of diskriptif of data BIPP and farmer group for analyzing swot can be determinad alternatif strategy. Result of research show alatematif strategy to improve profits of farmer group exploeted extension agent diging specific iptek, optimal farmer and lokalita of natural with appropriate agroklimat, form of exploiting of fisherman farmer and increase product pledge commodity and cxccd agriculture which orienting agribisnis.